Implementasi Wajib Belajar dalam Undang-Undang No 20 Tahun 2003 Ditinjau dari Fiqh Siyasah Tanfidziyah (Studi Kasus tentang Wajib Belajar di Nagari Koto Laweh Kecamatan Lembang Jaya Kabupaten Solok) - Fitri Yunita; Busyro (Lembaga Yasin AlSys, 2026)
Although the government has established a compulsory education program through Law Number 20 of 2003 concerning the National Education System, school-age children who have dropped out of school are still found in Nagari Koto Laweh, Lembang Jaya Subdistrict, Solok Regency. This study aims to analyze the efforts of the Nagari Koto Laweh Government in implementing the nine-year compulsory education program, identify the constraints on its implementation, and examine it from the perspective of fiqh siyasah tanfidziyah. This study employed a descriptive qualitative approach with a field research design. Data were collected through observation, interviews, and documentation and then analyzed descriptively and qualitatively. The results showed that the Nagari Koto Laweh Government had sought to implement the compulsory education program by providing educational facilities, distributing school supplies, collecting data on school-age children and school dropouts, raising awareness of the importance of education, and developing equivalency education programs for children unable to participate in formal education. However, the implementation of the program still faced several constraints, including limited parental attention to children’s education, family economic limitations, low learning motivation, the influence of the social environment, and early marriage. From the perspective of fiqh siyasah tanfidziyah, the implementation of the compulsory education program has reflected the government’s responsibility to fulfill the community’s right to education, but it has not been optimal because it has not fully satisfied the principles of justice, public benefit, deliberation, supervision, and balance between the rights and obligations of the government and the community. This study emphasizes the need to strengthen synergy among the nagari government, families, and the community so that the compulsory education program can be implemented more fairly, effectively, and with a greater orientation toward public benefit.